Breeding in bread-making wheat varieties for Mediterranean climate: the need to get resilient varieties - Maçãs, Benvindo; Costa, Rita; Gomes, Conceição; Bagulho, Ana Sofia; Pinheiro, Nuno; Moreira, José; Costa, Armindo; Patanita, Manuel; Dores, José; Rodrigo, Sara (Frontiers in Nutrition, 2024)
Being one of the “big three” most cultivated cereals in the world, wheat plays a crucial role in ensuring global food/nutrition security, supplying close to 20% of the global needs of calories and proteins. However, the increasingly large fluctuations between years, in temperatures and precipitation due to climate change, causes important variations in wheat production worldwide. This fact makes wheat breeding programmes a tool that, far from going out of fashion, is becoming the most important solution to develop varieties that can provide humanity with the sufficient amount of food it demands, without forgetting the objective of quality. National Institute of Agricultural and Veterinary Research in Portugal has carried out a long-term experiment (nine years) in different locations, to test four different bread-making wheat cultivars representing important variations in germplasm. Wheat yield and quality traits obtained by official methods, were recorded in 18 different environments regarding to temperature and precipitations. According to the ANOVA and PCA, protein content, wet gluten, and dough tenacity and extensibility, showed to be highly affected by the environment. Paiva cultivar presented the higher yield in almost all the tested environments, but its quality traits varied enormously. Contrary behavior was recorded for Valbona cultivar. Antequera cultivar, with a production ranging between 4.7 and 9.3 ton/ha and a protein content between 11 and 16,8 %, seems to be the most resilient cultivar regarding both, productivity and quality of the flour with reference to changes in the main climate traits. The most ancient cultivar, Roxo, released in 1996, showed the worst results in this experiment, supporting the need of continue working in wheat breeding to meet the unavoidable changes in the environments.